2015
DOI: 10.1152/ajprenal.00127.2015
|View full text |Cite
|
Sign up to set email alerts
|

Incipient renal transplant dysfunction associates with tubular syndecan-1 expression and shedding

Abstract: Syndecan-1 is a transmembrane heparan sulfate proteoglycan involved in regenerative growth and cellular adhesion. We hypothesized that the induction of tubular syndecan-1 is a repair response to incipient renal damage in apparently stable, uncomplicated renal transplant recipients. We quantified tubular syndecan-1 in unselected renal protocol biopsies taken 1 yr after transplantation. Spearman rank correlation analysis revealed an inverse correlation between tubular syndecan-1 expression and creatinine clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 53 publications
5
40
2
Order By: Relevance
“…Syndecan-1 is suggested as a tissue repair response marker. Upon injury, syndecan-1 is upregulated and involved in tissue repair responses in different organs such as the skin (11) or the kidneys (2,8). As a result of cellular shedding, an increase of plasma syndecan-1 levels can be acutely induced by a number of different stimuli such as major surgery, inflammatory insults, ischemia-reperfusion, shock, and also during HD (16,24), leading to a lower responsiveness status of the cells of origin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Syndecan-1 is suggested as a tissue repair response marker. Upon injury, syndecan-1 is upregulated and involved in tissue repair responses in different organs such as the skin (11) or the kidneys (2,8). As a result of cellular shedding, an increase of plasma syndecan-1 levels can be acutely induced by a number of different stimuli such as major surgery, inflammatory insults, ischemia-reperfusion, shock, and also during HD (16,24), leading to a lower responsiveness status of the cells of origin.…”
Section: Introductionmentioning
confidence: 99%
“…Syndecan-1 is expressed in many cell types during development but is downregulated in most cells after birth (6). In adults, syndecan-1 is mainly expressed by hepatocytes (28), epithelial cells (2), and plasma cells (30). Elevated plasma syndecan-1 is usually interpreted as endothelial glycocalyx loss and/or shedding from the (renal) epithelium and/or the liver (1,2,43).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in human renal transplant recipients have confirmed the clinical relevance of perlecan expression in kidney rejection, as higher serum or urinary levels of the perlecan C-terminal fragment associate with acute vascular rejection or advanced chronic allograft nephropathy, respectively (71,72). A recent translational study by Adepu and colleagues also implicated the HS syndecan-1 as important in contributing to graft outcomes in experimental and clinical kidney transplantation (73).…”
Section: Evolving Paradigms For Damps In Sotmentioning
confidence: 92%
“…While the immunomodulatory properties of Sdc-1 have been established in mouse models of inflammation, there is little data on the potential role of Sdc-1 in transplantation. In kidney transplant patients and animal models, increased tubular Sdc-1 expression was suggested to promote tubular survival and repair, while increased Sdc-1 plasma levels reflected early loss of tubular function (14, 19). The effect of Sdc-1 deficiency on allograft survival was not investigated.…”
Section: Introductionmentioning
confidence: 99%